BOOK REVIEWS (Journal of Finance, 1966)
Book reviewed in this article: Aggregate Theory and Policy : Modern Capital Theory. By D onald D ewey . Aggregate Theory and Policy : Readings in Macroeconomics. Edited by M. G. M ueller . Aggregate Theory and Policy : National Economic Policy. By J ames T obin . Business Finance and Investments : Business Finance: Theory and Management. By S tephen H. A rcher and C harles A. D'A mbrosio . Business Finance and Investments : The Economics of Corporate Finance. By S eymour F riedland . Business Finance and Investments : Efficiency of Investment in a Socialist Economy. Edited by M ieczystaw R akowski . Financial Institutions and Markets : Money and Finance: Readings in Theory, Policy, & Institutions. Edited by D eane C arson . Financial Institutions and Markets : Commercial Bank Behavior and Economic Activity: A Structural Study of Monetary Policy in the Postwar United States. By S tephen M. G oldfeld . International Finance : Financing African Development. Edited by T om J. F arer . International Finance : Central Banking in the Commonwealth. By J. O basanmi O lakanpo . International Finance : International Monetary Relations: Theory, History, and Policy. By L eland B. Y eager . Public Finance : Federal Budget Projections. By G erhard C olm and P eter W agner .